Correlating Symmetries of Low‐Frequency Vibrations and Self‐Trapped Excitons in Layered Perovskites for Light Emission with Different Colors. Issue 15 (26th February 2022) - Lin, Miao‐Ling; Dhanabalan, Balaji; Biffi, Giulia; Leng, Yu‐Chen; Kutkan, Seda; Arciniegas, Milena P.; Tan, Ping‐Heng; Krahne, Roman
Abstract: The soft hybrid organic–inorganic structure of two‐dimensional layered perovskites (2DLPs) enables broadband emission at room temperature from a single material, which makes 2DLPs promising sources for solid‐state white lighting, yet with low efficiency. The underlying photophysics involves self‐trapping of excitons favored by distortions of the inorganic lattice and coupling to phonons, where the mechanism is still under debate. 2DLPs with different organic moieties and emission ranging from self‐trapped exciton (STE)‐dominated white light to blue band‐edge photoluminescence are investigated. Detailed insights into the directional symmetries of phonon modes are gained using angle‐resolved polarized Raman spectroscopy and are correlated to the temperature‐dependence of the STE emission. It is demonstrated that weak STE bands at low‐temperature are linked to in‐plane phonons, and efficient room‐temperature STE emission to more complex coupling to several phonon modes with out‐of‐plane components. Thereby, a unique view is provided into the lattice deformations and recombination dynamics that are key to designing more efficient materials. Abstract : The directionality and the spatial symmetries of the fundamental vibrational modes in 2D layered perovskites are investigated by angle‐resolved Raman spectroscopy in the ultralow frequency regime. This provides valuable insights on possible electron‐lattice coupling mechanisms that can generate transient lattice deformations in such soft materials, which are at the base of self‐trapping of excitons and broadband emission of these materials.